Comparative effectiveness of different probiotics supplements for triple helicobacter pylori eradication: a network meta-analysis - Wang, Yue; Wang, Xue; Cao, Xue-Yan; Zhu, Han-Long; Miao, Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Probiotics has been reported as an effective supplement for Helicobacter pylori eradication. However, knowledge of their comparative efficacy is still lacking. Aim: In this study, we used network meta-analysis of current probiotics therapies used in triple therapy to assess and rank their comparative effectiveness. Methods: All randomized controlled trials from three databases (PubMed, Embase and Cochrane Library) up to April 2022 were collected and filtered to meet our criterion. We used Bayesian network meta-analysis to evaluate the eligible randomized controlled trials and gave a rank for the efficiency and incidence of side effects of each probiotics. The ranking probability for each therapy was assessed by means of surfaces under cumulative ranking values. Subgroup analysis was used to evaluate other influencing factors. Results: 34 eligible randomized controlled trials entered the following meta-analysis, including 9,024 patients randomized to 10 kinds of therapies. Result shows that most probiotics therapy had better outcomes than triple therapy, among which Bifidobacterium+Lactobacillus and Bifidobacterium+Lactobacillus+Saccharomyces adjuvant therapy could obtain comprehensive benefit with high eradication rate (78.3% and 88.2% respectively), and cause few side effects. Combination of different probiotics, adding probiotics before or after triple therapy and longer duration of probiotics can improve therapeutic effect in H pylori infected individuals. Conclusions: For triple therapy of H pylori infection, adding probiotics can increase eradication rate and bring protective effect. Considering the overall influence, Bifidobacterium+Lactobacillus or Bifidobacterium+Lactobacillus+Saccharomyces therapy can be a better choice in improving H.pylori eradication process.